EFEKTIVITAS PENGGUNAAN MEDIA INFOGRAFIS DALAM MENINGKATKAN PRESTASI BELAJAR PADA MATA PELAJARAN IPA - Ade Siskiatul Hikmah; Hafizah Ghany Hayudinna (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
Infographic media is a particular tool or format that combines data visualization, illustrations, text and images to convey or communicate information in an interesting way so that it is easily understood by the audience. The purpose of this study is to describe how the achievements of class V students who use infographic learning media, and those who do not use infographics learning media, and explain how effective the use of infographics learning media is to increase student achievement in science subjects in class V. This study uses a quasi-experimental approach. . The collection of data or instruments in this study was carried out by means of tests, observations and documentation. The data analysis technique used the Independent Simple T-Test test. The results showed that the value of tcount = 9.987 ttable = 2.024, so H0 was rejected and Ha was accepted, it can be concluded that the use of infographic media is effective in improving student achievement in science subjects for class students V.Keywords: Infographic Media, Learning Achievement, Science Subjects.